Efficiency and coordination in the EU agri-food systems - Simone Severini; Alessandro Sorrentino (Agricultural and Food Economics, 2017)
During the 52nd Conference of the Italian Society of Agricultural Economists (SIDEA), Italian agricultural economists have been given the opportunity to debate regarding internationalization, competition, and local development in agri-food systems. This special issue of the journal AFE contains four selected papers presented in this conference. These papers focus on three main issues that are strongly affecting the evolution of food supply-chains and their functioning mechanisms. These are the growing role of vertical integration between the farm sector and the downstream sectors, the possibility for farmers to increase their horizontal integration and the role of agricultural policies in affecting these phenomena. The reading of these papers allow for a better understanding of what is affecting the competitiveness of the EU agro-food system, the distribution of the bargaining power along the value-chain and, at the end, the efficiency and economic performances of the EU farm sector.
Keywords: 330; Agri-food value chain; Vertical coordination; Efficiency; Common agricultural policy